2022
DOI: 10.1002/mpr.1904
|View full text |Cite
|
Sign up to set email alerts
|

A mediational analysis of adverse experiences in childhood and quality of life in adulthood

Abstract: Objectives: This study examined associations of three prevalent adverse childhood experiences (ACEs) -parents' problematic alcohol use (PPAU), parental separation/ divorce, and lack of support from a trusted adult-with adult quality of life (QoL), and potential mediators of associations.Methods: Data were from a representative survey (N = 28,047) in Norway that assessed ACEs, QoL, and potential mediators: enduring perceptions of childhood hardships (Difficult Childhood Questionnaire; DCQ), current mental distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Moreover, in accordance with several similar studies that have confirmed the associations between adverse childhood experiences and psychological wellbeing among young or older adults (Burns et al, 2022; Vederhus et al, 2022), the current results show that childhood bullying victimization significantly increases the possibility for middle and older adults to be trapped in social isolation, further improving their levels of depression. Specifically, exposure to childhood bullying victimization blocks the initial reserve of individuals’ interpersonal abilities at the early stage (Barile et al, 2015), causing them unable to obtain sufficient and high-quality social relationships to maintain mental health in the future (Uchino et al, 1996), and also damages their stress response regulation systems (Subramaniam et al, 2020), further forming stable negative coping strategies of avoidance and withdrawal (Bjereld, 2018), which is unfavorable for them to get out of the state of social isolation (Nicholson, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, in accordance with several similar studies that have confirmed the associations between adverse childhood experiences and psychological wellbeing among young or older adults (Burns et al, 2022; Vederhus et al, 2022), the current results show that childhood bullying victimization significantly increases the possibility for middle and older adults to be trapped in social isolation, further improving their levels of depression. Specifically, exposure to childhood bullying victimization blocks the initial reserve of individuals’ interpersonal abilities at the early stage (Barile et al, 2015), causing them unable to obtain sufficient and high-quality social relationships to maintain mental health in the future (Uchino et al, 1996), and also damages their stress response regulation systems (Subramaniam et al, 2020), further forming stable negative coping strategies of avoidance and withdrawal (Bjereld, 2018), which is unfavorable for them to get out of the state of social isolation (Nicholson, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…In the Chinese context, this issue is particularly pronounced due to the widespread phenomenon of “empty-nest elderly” resulting from rapid societal changes (Tang et al, 2021), which refers to the social phenomenon wherein adult children or grandchildren migrate from rural to urban areas or from the Midwest to the East of China for work or education, leaving their elderly parents or grandparents living alone. While previous research has predominantly focused on the association between functional health (e.g., cognitive function and physical function) on middle and older adults’ social isolation (Luo et al, 2021), emerging evidence suggests that childhood bullying victimization may also play a role in predicting social isolation in later life (Burns et al, 2022; Vederhus et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, adolescents who live in substitute care often experience traumatic events in their early lifespan (Salazar et al, 2013). Many clients of child welfare services and adolescent psychiatry have a history of manifold victimization and adverse childhood experiences (ACEs), such as physical, sexual or emotional abuse, mental illness of a household member, or substance abuse issues within the childhood family that usually accompany them in various ways into adulthood (Anda et al, 2006; Vederhus et al, 2022). Childhood cumulative trauma can cause long-term consequences and act as a predictor of increasing psychosocial symptom complexity in later years (Cloitre et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Parental separation proves to be stressful for most children and can affect their health as adults [1,[3][4][5]. Studies from recent years also include other aspects that can influence health and self-conceptual problems such as parent-child relations [2], custody arrangements [6][7][8][9] and children's experiences [7,10].…”
Section: Introductionmentioning
confidence: 99%